2005
DOI: 10.12693/aphyspola.108.429
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intermolecular Interactions in the Electro-Optical Kerr Effect in Liquid Alkanes

Abstract: The electro-optical Kerr effect of n-alkanes from C 5 to C 16 was investigated in gas phase, liquid phase, and solution. The values of the Kerr constants in gas phase are noticeably distinguishable from those in liquids, where the molecules interact by the London dispersion forces. Both the energy of the dispersion interaction and the difference in the Kerr constants in liquid and gas phase grow with molecular size, indicating the key influence of the interaction on the magnitude of the Kerr effect. Several or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Fits of Model Polarity Functions to the Data. The results of the calibration of the dependencies of indole and Nile Red absorption and fluorescence peak wavelengths on the dielectric constants 44,71,72 and the refractive indices (eqs 1−5) are shown in Figure 1A,B for indole and Nile Red, respectively, and summarized in Table 2. The error bars of the wavelength terms in Figure 1A,B are not shown because the standard errors of the means (SEMs) of the peak wavelengths (Table 1) lead to the errors of the wavelength terms, which are smaller than the diameter of the shown points.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fits of Model Polarity Functions to the Data. The results of the calibration of the dependencies of indole and Nile Red absorption and fluorescence peak wavelengths on the dielectric constants 44,71,72 and the refractive indices (eqs 1−5) are shown in Figure 1A,B for indole and Nile Red, respectively, and summarized in Table 2. The error bars of the wavelength terms in Figure 1A,B are not shown because the standard errors of the means (SEMs) of the peak wavelengths (Table 1) lead to the errors of the wavelength terms, which are smaller than the diameter of the shown points.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The results of the calibration of the dependencies of indole and Nile Red absorption and fluorescence peak wavelengths on the dielectric constants 44,71,72 1) lead to the errors of the wavelength terms, which are smaller than the diameter of the shown points. The errors range from 2.3×10 −6 nm −1 to 1.3×10 −5 nm −1 for indole (Figure 1A), and from 4.2×10 −7 nm −1 to 3.6×10 −6 nm −1 for Nile Red (Figure 1B).…”
Section: Fits Of Model Polarity Functions To the Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Early measurements have shown that the effect is usually small, although it cannot be neglected . Ground state DMs are commonly used for characterization of electronic charge distributions in molecules , and solute−solvent interactions. DMs of molecules in excited electronic states are more difficult to obtain. For this purpose one can use the dependence of optical absorption lines on the external electric field .…”
Section: Introductionmentioning
confidence: 99%